Community-Based Screening, Brief Intervention, and Referral for Treatment for Unhealthy Tobacco Use: Single Arm Study Experience and Implementation Success in Rural and Semi-Rural Settings, South-West Nigeria - Lasebikan, Victor Olufolahan; Ola, Bolanle Adeyemi (Frontiers in Psychiatry, 2016)
Objective: To determine whether Screening, Brief Intervention and Referral to Treatment (SBIRT) can reduce the prevalence of tobacco use in rural and semi-rural settings. Method: Design and participants: A non-randomized clinical trial with assessments at baseline and post-intervention assessments at 3 and 6 months was conducted in a rural and semi-rural district in South-West of Nigeria. A representative sample of 1203 persons consented to the study and had ASSIST administered to them by trained community healthcare extension workers between October, 2010 and April, 2011. Follow-up participation was more than 99% at all points. Intervention: Participants received a single ASSIST linked brief intervention (BI) and referral for treatment (RT) at entry, and a booster ASSIST BI and RT at 3 months. Main outcomes and measures: The primary outcome was self-reported scores on ASSIST. Results: At baseline, out of 1203 respondents, lifetime prevalence and current prevalence of any tobacco products was 405 (33.7%) and 248 (20.6%) respectively. Of the current users, on the ASSIST, 79 (31.9%) scored 0-3 (low health risk), 130 (52.4%) scored 4-26 (moderate risk), 39 (15.7%) scored 27+ (high risk). At 3 months, out of 1199 respondents, prevalence of current users was 199 (16.5%) and out of 1195 respondents, was 169 (14.1%) at 6 months. Prevalence of tobacco use reduced significantly at 3 months Z = -3.1, p = 0.01 and at 6 months when compared with baseline Z = 4.2, p = 0.001, but not at 6 months compared with at 3 months, Z = 2.1, p = 0.09. Multivariate analysis revealed that age at initiation of tobacco use, gender, marital status, setting of dwelling and socioeconomic status were the only variables that were associated with current tobacco use at baseline, 3 months and 6 months. Conclusion: A one-time BI with a booster at 3 months had a significant effect on tobacco use in persons living in community settings. This finding suggests a need for promoting the adoption of this intervention for tobacco use in rural and semi-rural community settings.